Programmable materials based on periodic cellular solids. Part I: Experiments. (1st December 2016) - Restrepo, David; Mankame, Nilesh D.; Zavattieri, Pablo D.
Highlights: We present a new type of programmable materials (PCMs) based on cellular solids. A shape memory polymer is used as the base material. Programing allows modifying the properties of a programmable material. Programing is reversible and repeatable. Significant changes in the response of PCMs is achieved by programing. Abstract: We introduce a new class of programmable materials whose effective mechanical properties can be modified after manufacturing without any additional reprocessing. Programing is achieved by the controlled introduction of a morphological imperfection into the unit cell of a periodic cellular solid which triggers changes in the effective mechanical properties of these materials. Two programmable material systems are studied in this work: a bending dominated honeycomb with a hexagonal unit cell and a stretching dominated honeycomb with a kagome unit cell. A shape memory polymer is used as the base material and the cellular materials are programed using the standard shape fixing process for shape memory polymers. We show that significant changes in the effective mechanical properties can be attained with low values of programed strains. For instance, a programed imperfection corresponding to a global compressive strain of 5% in the bending dominated system leads to a 55% increase in initial in-plane effective elastic Young's modulus, an 81% increase in the propagation stress for in-plane compression and a 30% reduction in the out-of-plane effective flexural modulus. The bending dominated system shows a linear change in effective properties with programing up to 10% global programed strain, whereas the stretching dominated system shows a rapid initial change in effective properties with low values of global programed strain (< 2% global strain), but the rate of change saturates quickly. Some programmable material systems are amenable to bi-directional modulation (i.e. increase or decrease) of effective properties of the material through suitable programing. Graphical abstract: